Perubahan struktur organisasi: Bagaimana implikasinya terhadap peluang karier dan perilaku kewargaan organisasi? - Wahyudi Wahyudi; Udin Bahrudin; Edy Suranta Karina Sembiring (Jurnal Integrasi Sumber Daya Manusia, 2022)
Organizational structures that are more complex and innovative are starting to develop, especially in large companies but bring new challenges in their implementation. This study examines the implications of organizational structure changes on employee career opportunities and organizational citizenship behavior. This research was conducted at PT. XYZ is in the department of Human Resource Development (HRD) with a total population of 97 people, while the sample used is saturated. The method used is PLS-SEM using the SmartPLS software tool. As a result, organizational structure changes negatively affect organizational citizenship behavior but positively affect career opportunities. While career opportunities have a positive and significant effect on organizational citizenship behavior, on the other hand, career opportunities can indirectly affect organizational structure changes and organizational citizenship behavior in a positive and significant way.